Utilization of chico (Achras sapota) and tiessa (Pouteria camphechiana) in fruity muffin - Pancho, Portia Pauleth Osunero (2011.)
Local nutritious fruits namely chico (Achras sapota) and tiessa (Pouteria camphechiana) were tested for fruity muffin production.
Sotech thesis.
Keywords: Chico--Achras sapota; Tiesa--Pouteria camphechiana; Fruity muffin